DIGITIZING HISTORICAL MOTIVES: MEDIA INSTEAD OF CULTURAL ARTIFACTS - Bukhari, Bukhari; rahman, Aulia; Riyani, Mufti (INTERNATIONAL JOURNAL ON LANGUAGE, RESEARCH AND EDUCATION STUDIES, 2020)
The advancement of digital technology in the era of the 4.0 Industrial Revolution has been a major challenge for the timing of historians. Historians are required to be increasingly cosmopolitan in the approach used. Research methods including data search and historical sources and dissemination models are expected to adapt or discover new ways. The purpose of this research is to produce a digital model with two main objectives, first allowing the availability of data banks in the form of information sources that are scientifically related to the historical motif of coastal ornaments in the eastern Aceh region. Secondly, it became a contemporary historical dissemination media. This research is based on historical studies with archaeological and anthropological approaches through the search of various decorative media. As a form of applied research, the next stage continues to develop the historical motif into a digital model that can be utilized as an alternative study of history.  Keywords: Cultural Artifacts, Digitization, Dissemination, Historical Motives, East       Aceh